Effect of B, Si and P Co-doping on Electronic Properties of Mn-doped AlN Crystals - Syrotyuk, S.V.; Shved, V.M. (Ukrainian Journal of Physics, 2022)
The partial and total electron state densities of Mn-doped AlN crystals co-doped with B, Si, and P atoms are calculated for the up and down orientations of the spin moment. The comparison of the electron state densities of pure and Mn-doped AlN crystals shows that the Mn impurity leads to the appearance of hybridized energy states with p- and d-symmetry in the forbidden band. The co-doping with B, Si, and P atoms results in a change of the electron state density and the spin magnetic moments on all atoms of the crystal.